2012
DOI: 10.1016/j.juro.2011.10.125
|View full text |Cite
|
Sign up to set email alerts
|

Association of Randall Plaque With Collagen Fibers and Membrane Vesicles

Abstract: Background Idiopathic calcium oxalate (CaOx) kidney stones develop by deposition of CaOx crystals on Randall's plaques (RP). Mechanisms involved in RP formation are still unclear. Objective It is our hypotheses that RP formation is similar to vascular calcification involving components of extracellular matrix including membrane bound vesicles (MV) and collagen fibers. In order to verify our hypothesis we critically examined renal papillary tissue from stone patients. Methods 4 mm cold-cup biopies of renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 27 publications
4
117
0
2
Order By: Relevance
“…This peripheral growth in calcification continues through heterogeneous nucleation of these crystals and the surrounding milieu. This process of ectopic calcification is similar to pathologic calcifications within atherosclerotic lesions [13].…”
supporting
confidence: 54%
“…This peripheral growth in calcification continues through heterogeneous nucleation of these crystals and the surrounding milieu. This process of ectopic calcification is similar to pathologic calcifications within atherosclerotic lesions [13].…”
supporting
confidence: 54%
“…These precipitations would in turn cause the clinical sequelae of AMI and stroke observed herein. Consistent with this, a recent study found that the formation of Randall plaque (the inciting stone nidus) is similar in composition to vascular plaque (24). Moreover, inhibitors of calcification are found both in blood and urine, such as pyrophosphates (25).…”
Section: Potential Mechanisms For the Findingsmentioning
confidence: 61%
“…Khan et al studied papillary biopsies from ICSF with light microscopy, TEM, SEM, and IHC for osteopontin and collagen [31]. Plaque mineral does not come in direct contact with urine.…”
Section: Role Of Collagen and Membrane Vesiclesmentioning
confidence: 99%
“…There is loss of epithelium at plaque surface. This exposes a fibrous layer and plaque is beneath this fibrous layer [31]. Outer surface of plaque is composed of small spherical units mixed with long thin fibers running between them.…”
Section: Role Of Collagen and Membrane Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation